2014
DOI: 10.1186/1471-244x-14-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Canadian clinical practice guidelines for the management of anxiety, posttraumatic stress and obsessive-compulsive disorders

Abstract: BackgroundAnxiety and related disorders are among the most common mental disorders, with lifetime prevalence reportedly as high as 31%. Unfortunately, anxiety disorders are under-diagnosed and under-treated.MethodsThese guidelines were developed by Canadian experts in anxiety and related disorders through a consensus process. Data on the epidemiology, diagnosis, and treatment (psychological and pharmacological) were obtained through MEDLINE, PsycINFO, and manual searches (1980–2012). Treatment strategies were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
574
3
25

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(610 citation statements)
references
References 1,396 publications
(1,681 reference statements)
8
574
3
25
Order By: Relevance
“…at least once a week), highlighting an opportunity for improvement in the care and management of such individuals. Even though physical activity/exercise is usually considered an adjunct therapy to conventional clinical treatment (medication and/or psychotherapy) in most clinical guidelines, [34][35][36] it could also be used as a first-line, low-intensity intervention for mild-to-moderate mood and anxiety disorders, along with other self-management strategies. 6,37,38 Findings from this study show that affected Canadians who were less likely to engage in physical activity/exercise were older, less educated, belonged to the lowest income quintiles and resided in Ontario and the Atlantic provinces compared to those who engaged.…”
Section: Discussionmentioning
confidence: 99%
“…at least once a week), highlighting an opportunity for improvement in the care and management of such individuals. Even though physical activity/exercise is usually considered an adjunct therapy to conventional clinical treatment (medication and/or psychotherapy) in most clinical guidelines, [34][35][36] it could also be used as a first-line, low-intensity intervention for mild-to-moderate mood and anxiety disorders, along with other self-management strategies. 6,37,38 Findings from this study show that affected Canadians who were less likely to engage in physical activity/exercise were older, less educated, belonged to the lowest income quintiles and resided in Ontario and the Atlantic provinces compared to those who engaged.…”
Section: Discussionmentioning
confidence: 99%
“…Zbog toge postoji preporuka je da se pacijentima sa generalizovanim anksioznim poremećajem za početak lečenja odredi terapija koja je pokazala efikasnost, a nema neželjena dejstva koja mogu da kompromituju tretman [5,6]. Pored toga, treba da se obrati pažnja na eventualno postojanje komorbidih oboljenja (pre svega depresije), ali i na praktične aspekte -kao što su iskustva sa terapijom, dostupnost terapije i lekara za buduće kontrole, ekonomske mogućnosti pacijenta, preference samog pacijenta i slično.…”
Section: Uvodunclassified
“…Što se tiče farmakoterapije, na osnovu kliničkog iskustva i na osnovu rezultata kliničkih studija, a na bazi potvrđene efikasnosti i najbenignijeg profila neže-ljenih dejstava, preporuka je da se pacijenti sa generalizovanim anksioznim poremećajem tretiraju nekim lekom iz grupe SSRI antidepresiva (citalopram, escitalopram, fluoksetin, paroksetin, sertralin), nekim lekom iz grupe iz grupe SNRI antidepresiva (duloksetin ili venlafaksin) ili pregabalinom, ukoliko ne postoje simptomi komorbidne depresije [5,6,7].…”
Section: Uvodunclassified
“…Once the diagnosis has been explained to the patient, it is often reasonable to give a hopeful prognosis, outline the available treatments and negotiate a treatment package. Table 2) have been shown to be effective against the symptoms of panic disorder 13,14 and clinical studies have demonstrated high rates of efficacy -up to 80 per cent in some trials using drugs originally developed for depression (antidepressants). Among antidepressants, citalopram, escitalopram, paroxetine, sertraline and certain formulations of venlafaxine are licensed specifically for panic disorder.…”
Section: Treatment Of Panic Disordermentioning
confidence: 99%